1994
DOI: 10.1111/j.1471-0528.1994.tb13652.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of prophylaxis of post‐abortal infection: ceftriaxone versus placebo

Abstract: Objective To investigate the incidence of post‐operative infection after first trimester abortion in women treated with a long‐acting cephalosporin (ceftriaxone) compared with low risk patients receiving no treatment and with high risk patients receiving our standard treatment of ampicillin/pivampicillin and metronidazole. Design A prospective, randomised controlled trial. Setting Department of Obstetrics and Gynaecology, Rigshospitalet, University of Copenhagen, Denmark. Subjects Nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Fourteen of the 23 studies reported ≥5.0% of cases later developed infections requiring outpatient antibiotics, although seven studies did not explicitly report outpatient treatment for non-hospitalized cases of endometritis and PID [36,37,[40][41][42]50,54]. Most studies in which ≥5.0% of women received outpatient treatment for infection noted that women were tested for Chlamydia prior to the procedure, and two provided antibiotic prophylaxis to those with positive results [39,46].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Fourteen of the 23 studies reported ≥5.0% of cases later developed infections requiring outpatient antibiotics, although seven studies did not explicitly report outpatient treatment for non-hospitalized cases of endometritis and PID [36,37,[40][41][42]50,54]. Most studies in which ≥5.0% of women received outpatient treatment for infection noted that women were tested for Chlamydia prior to the procedure, and two provided antibiotic prophylaxis to those with positive results [39,46].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The majority of hospital-based studies reported ≥1.0% of women hospitalized for complications, and many were conducted in Scandinavian countries in the 1980's and early 1990's. Women in these studies were hospitalized primarily to treat PID or for abdominal procedures; one study did not specify the reasons for hospitalization [54], and two others noted that some women experiencing complications were hospitalized for 'social' or 'geographic' reasons, [36,45] suggesting that the percentages reported may not reflect the women were screened prior to the procedure, and those who were not considered good candidates for deep sedation (e.g., body mass index >40kg/m 2 , poorly controlled seizure disorder or asthma) or who did not follow fasting guidelines were referred to a hospital or had the procedure performed using local anesthesia.…”
Section: Hospitalizationmentioning
confidence: 99%
“…8,[10][11][12] Both measurements were separately taken 2 times with bare feet. If the first 2 measurements differed by 1 cm or 200 g for height or weight, a third measurement was taken for the average calculation.…”
Section: Other Measurements and Covariatesmentioning
confidence: 99%
“…10 It has been reported that endothelium-dependent vasodilation is increased in women who have preeclampsia to levels over and above those seen in normal pregnancy. 11 Nonetheless, whether maternal blood pressure is associated with microvascular changes that may lead to poor maternal and neonatal outcomes is uncertain because of a lack of means to visualize and assess the microcirculation directly. Over the last decade, the retinal microcirculation has been established as a "biological model" to study the human microcirculation in vivo.…”
mentioning
confidence: 99%
“…Eight randomized trials on antibiotic prophylaxis for first‐trimester suction curettage and 1 randomized trial involving second‐trimesterdilation and evacuation were identified [11–19]. No trials of dilation and curettage without products of conception met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%